2021
DOI: 10.1101/lm.053041.120
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of glucocorticoid receptors in cortical astrocytes to memory recall

Abstract: Dysfunctions in memory recall lead to pathological fear; a hallmark of trauma-related disorders, like posttraumatic stress disorder (PTSD). Both, heightened recall of an association between a cue and trauma, as well as impoverished recall that a previously trauma-related cue is no longer a threat, result in a debilitating fear toward the cue. Glucocorticoid-mediated action via the glucocorticoid receptor (GR) influences memory recall. This literature has primarily focused on GRs expressed in neurons or ignored… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
1
3
0
Order By: Relevance
“…Freezing during the inter-trial intervals also did not differ between the sexes ( Supplementary Figure 1A ). As sex differences in passive vs. active conditioned threat responses have been reported ( Gruene et al, 2015 ), we next quantified instances of darting and found no evidence of sex differences in conditioned flight behavior ( Supplementary Figure 1B ), similar to previous investigations in C57Bl/6J mice ( Borkar et al, 2020 ; Florido et al, 2021 ; Taylor et al, 2021 ). Finally, we observed no sex differences in average shock reactivity (two-tailed t -test, p = 0.21; Figure 1C ) or shock reactivity across CS-US trials ( Supplementary Figure 1C ).…”
Section: Resultssupporting
confidence: 80%
“…Freezing during the inter-trial intervals also did not differ between the sexes ( Supplementary Figure 1A ). As sex differences in passive vs. active conditioned threat responses have been reported ( Gruene et al, 2015 ), we next quantified instances of darting and found no evidence of sex differences in conditioned flight behavior ( Supplementary Figure 1B ), similar to previous investigations in C57Bl/6J mice ( Borkar et al, 2020 ; Florido et al, 2021 ; Taylor et al, 2021 ). Finally, we observed no sex differences in average shock reactivity (two-tailed t -test, p = 0.21; Figure 1C ) or shock reactivity across CS-US trials ( Supplementary Figure 1C ).…”
Section: Resultssupporting
confidence: 80%
“…Several publications have reported the existence of sexual differences as a global feature of brain functioning (Alshammari, 2021; Berchtold et al, 2008; Cieri et al, 2022; del Mauro et al, 2022; Guebel et al, 2016; Mazur et al, 2021; Pallayova et al, 2019; Taylor et al, 2021; Yang et al, 2021). Therefore, herein it was tested whether this phenomenon also occurs in the astrocytic population.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the systematic characterization of numerous differential astrocytic features linked to sex was notably possible (Sections 3.4 and 3.5). The occurrence of sexual differences in astrocytes is relevant because this feature has often been ignored even when individuals of both sexes were included in the studies (Chai et al, 2017;Lanke et al, 2018), or sex differences was sought, but only in relation to a unique molecule (Johnson et al, 2008;Lennol et al, 2021;Mazur et al, 2021;Morrison & Filosa, 2016;Sanfilippo et al, 2019Sanfilippo et al, , 2020Santos-Galindo et al, 2011;Taylor et al, 2021). An exception is the work of Krawczyk et al (2022) who investigated sexual differences in human cortical astrocytes at a general level, but in a tumoural environment.…”
Section: Discussionmentioning
confidence: 99%
“…For many years, researchers have confined the latter to assistance functions, energy supply, waste evacuation, immune surveillance, etc. However, several recent studies emphasize their participation in information processing (Henneberger et al, 2020;Fields & Bukalo, 2020;Li et al, 2020;Taylor et al 2021); -finally, learning changes the landscape of neuronal connections and thus the processing of new information.…”
Section: Neural Codes and Plastic Engrams: The Primary Artifacts Of T...mentioning
confidence: 99%